Alterations in the Mineral Bone Metabolism of Living Kidney Donors After Uni-Nephrectomy: Prospective Observational Study - Lee, Hanbi; Eum, Sang Hun; Ko, Eun Jeong; Cho, Hyuck Jin; Yang, Chul Woo; Chung, Byung Ha (Frontiers in Medicine, 2021)
We investigated the dynamic change of mineral bone metabolism and explored factors associated with the alteration of mineral bone metabolism in living kidney donors (LKDs) after uni-nephrectomy. One-hundred forty-four prospective LKDs who underwent kidney donation between May 2016 and September 2018 were enrolled. Laboratory evaluation regarding mineral bone metabolism, including intact PTH (iPTH), renal fractional excretion of phosphate (FEPi), and Technetium-99m diethylene-triamine-pentaacetate (99mTc-DTPA) scan were performed pre-donation and six months after donation. We divided donors into two groups, the low △FEPi and high △FEPi groups, according to the change of FEPi after donation, and investigated significant risk factors associated with high △FEPi. At six months after uni-nephrectomy, estimated GFR (eGFR) significantly declined by 30.95 ml/min/1.73m2 (p<.001), but the mGFR of the remaining kidney by 99mTc-DTPA scan showed significant increase. Serum phosphorus decreased (p<.001), whereas FEPi (13.34 to 20.23%, p<.001) and serum iPTH (38.70 to 52.20 pg/ml, p<.001) showed significant increase. In the high △FEPi group, the proportion of pre-existing hypertension (HTN) was higher, the baseline FEPi was lower, and percent decline in eGFR was greater. Moreover, all of these factors were independently associated with high △FEPi upon multivariable logistic regression analysis. LKDs showed a significant change in mineral bone metabolism after uni-nephrectomy especially when donors had pre-existing HTN, lower baseline FEPi, and showed greater loss of kidney function. Hence, strict monitoring of mineral bone metabolism parameters and bone health may be required for these donors.